Corporate Social Responsibility and Environmental Protection in the Nigerian Energy Sector: Reflection on Issues and Legal Reform - Abdulkadir, Abdulkadir Bolaji (Journal of Sustainable Development Law and Policy, 2025)
The abatement of environmental degradation has been an issue which has received growing attention in recent times. Despite the increased attention however, environment pollution has remained unabated in Nigeria with its adverse impacts on the citizens. The question then is, do businesses owe society any social responsibility as it relates to the protection of environment? The Energy sector in Nigeria plays a very crucial role in Nigeria’s development, as the industrial development and innovation necessary for the economic development of any country is directly linked to the management of energy resources. Nigeria is endowed with abundant (fossil fuel) energy resources, such as oil, gas, coal, fuel wood, etc., which are dominantly the fuel sources for electrical energy production, yet, Nigeria is faced with environmental challenges capable of limiting and destroying access to these energy resources without taking cognizance of their environmental control. Therefore, this article attempts at navigating the imperative of Corporate Social Responsibility. Furthermore, the use of Corporate Social Responsibility as a tool for abatement and prevention of environmental damage to the energy sector is considered. Finally, possible recommendations were made as control measure through CSR in Nigeria in order to protect the energy resources and ensure a clean and healthy environment.